2020
DOI: 10.1163/1876312x-00001027
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Neotropical butterfly genus Paryphthimoides Forster, 1964 (Lepidoptera: Nymphalidae: Satyrinae), with descriptions of seven new taxa

Abstract: A systematic revision of Paryphthimoides, a satyrine genus widely distributed in Central and South America, is presented based on an integrative approach. Molecular phylogeny inferred using multiple methods with nuclear (GAPDH, RpS5) and mitochondrial (COI) genes indicates that Paryphthimoides, as currently circumscribed, is polyphyletic. A new taxonomic arrangement is proposed reflecting the monophyly based on molecular and morphological evidence. Paryphthimoides now comprises 14 taxa, namely: P. poltys polty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
8
0
3
Order By: Relevance
“…Butterflies were identified to species and subspecies level using online guides (e.g., www.butterfliesofamerica.com, www.neotropicalbutterflies.com) and the taxonomic literature [51][52][53][54][55]. We used taxonomic references to confirm the current taxonomy of cryptic butterflies [56][57][58][59][60][61][62][63] and all butterfly identifications were verified by an expert…”
Section: Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Butterflies were identified to species and subspecies level using online guides (e.g., www.butterfliesofamerica.com, www.neotropicalbutterflies.com) and the taxonomic literature [51][52][53][54][55]. We used taxonomic references to confirm the current taxonomy of cryptic butterflies [56][57][58][59][60][61][62][63] and all butterfly identifications were verified by an expert…”
Section: Sampling Designmentioning
confidence: 99%
“…Butterflies were identified to species and subspecies level using online guides (e.g., www.butterfliesofamerica.com, www.neotropicalbutterflies.com) and the taxonomic literature [51][52][53][54][55]. We used taxonomic references to confirm the current taxonomy of cryptic butterflies [56][57][58][59][60][61][62][63] and all butterfly identifications were verified by an expert taxonomist. All collected butterflies were deposited in the Entomological Collection of the National Institute of Amazonian Research (INPA) and some individuals of the most abundant species were also deposited in the Zoological Collection of the Federal University of Amazonas (UFAM) and at the National Museum (UFRJ).…”
Section: Sampling Designmentioning
confidence: 99%
“…A detailed study by Zacca et al . (2020) on the systematics of the genus Paryphthimoides Forster 1964 using data from morphology, mitochondrial and nuclear DNA, and geographic distribution has demonstrated that the genus, as previously circumscribed by Lamas (2004) is polyphyletic. As result, a new taxonomic arrangement was proposed, which excluded nine species from Paryphthimoides .…”
Section: Introductionmentioning
confidence: 83%
“…were placed in Magneuptychia (Benmesbah et al, 2018;Lamas, 2004). As discussed by Zacca, Casagrande, et al (2018), most species placed in Cissia prior to that paper were presumably considered to be related because of their possession of a yellowish patch on the VFW, but that character is clearly homoplasious, and the Cissia of Lamas (2004)…”
Section: Description (Figuresmentioning
confidence: 99%
“…In recognition of these problems, the last 15 years have seen an explosion of interest in the group, including generic revisions (e.g. Freitas & Peña, 2006; Nakahara, Lamas, et al, 2019; Nakahara, Rodríguez‐Melgarejo, et al, 2022; Nakahara, Zacca, et al, 2018, 2019; Peña & Lamas, 2005; Willmott et al, 2019; Zacca et al, 2013; Zacca, Casagrande, et al, 2018; Zacca, Casagrande, Mielke, Huertas, Barbosa, Freitas, et al, 2020; Zacca, Casagrande, Mielke, Huertas, Espeland, Freitas, et al, 2020; Zacca, Paluch, et al, 2017), descriptions of life histories (e.g. Baine et al, 2019; Corahua‐Espinoza et al, 2023; Corahua‐Espinoza, Nakahara, Kabir, et al, 2022; Corahua‐Espinoza, Nakahara, Shellman, et al, 2022; Cosmo et al, 2014; Freitas, 2004, 2017, 2022; Freitas, Barbosa, & Carreira, 2021; Freitas, Barbosa, & Marín, 2016; Freitas, Carreira, Santos, & Barbosa, 2016; Freitas, Mota, Barbosa, & Carreira, 2019; Freitas, Rosa, et al, 2018; Freitas, Rosa, & Kaminski, 2021; Hurtado et al, 2021; Kaminski & Freitas, 2008; Nakahara, Hoffman, et al, 2020; See et al, 2018; Tejeira et al, 2021), and papers addressing the higher level phylogenetic relationships, using both morphology (Marín et al, 2017) and molecular (Espeland et al, 2019a; Murray & Prowell, 2005; Peña et al, 2010) datasets.…”
Section: Introductionmentioning
confidence: 99%